2022
DOI: 10.2991/assehr.k.220108.082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Civics Textbooks in Framework of the 21st Century Learning

Abstract: The goal of this study is to have a better understanding of Civics Class X texts in the context of the 21st Century Learning Framework. Students in the 21st century are expected to have a variety of abilities, critical thinking and problem solving, creativity and invention, communication, and cooperation are just a few of the skills you'll learn. Textbooks are instruments that help students gain new skills and information. Civics textbooks are a valuable resource for students who want to increase their civics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The implementation of continuous learning by utilizing information technology such as images of the Pancasila symbol, videos of Pancasila implementation, images of diversity in Indonesia, and videos of attitudes towards diversity obtained from the internet and broadcast using laptops via projectors shows that the principle of sustainable future-oriented learning diversity has been pursued in schools. Ideally, the principle of sustainable future-oriented learning is pursued in a number of activities such as involving technology to acquire knowledge, and teaching 21st century skills to students (Saputra & Abdulkarim, 2021;Sufyadi et al, 2021). Searching for sources of information via the internet and computer devices demonstrates the application of this principle.…”
Section: Collaboration and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of continuous learning by utilizing information technology such as images of the Pancasila symbol, videos of Pancasila implementation, images of diversity in Indonesia, and videos of attitudes towards diversity obtained from the internet and broadcast using laptops via projectors shows that the principle of sustainable future-oriented learning diversity has been pursued in schools. Ideally, the principle of sustainable future-oriented learning is pursued in a number of activities such as involving technology to acquire knowledge, and teaching 21st century skills to students (Saputra & Abdulkarim, 2021;Sufyadi et al, 2021). Searching for sources of information via the internet and computer devices demonstrates the application of this principle.…”
Section: Collaboration and Discussionmentioning
confidence: 99%
“…Fourth, references regarding the implementation of the Merdeka Curriculum in learning are needed by teachers. This urgency encouraged researchers to conduct This research provides novelty by presenting a study of the implementation of the New Paradigm of the Merdeka Curriculum, especially in Pancasila Education Learning in first-generation schools, compared to several previous studies, whose research results concluded based on a literature review so that it has limitations in reviewing the implementation of learning in the field directly (Herwina, 2021;Saputra & Abdulkarim, 2021;Zalik & Saidi, Mahmuda, 2020). This study helps schools analyse the intervention process carried out by teachers in schools in implementing the new paradigm of the Merdeka Curriculum in Pancasila Education learning.…”
Section: Introductionmentioning
confidence: 99%